Pembangunan Website Point of Sale Pada Kafe Opak Kopi - Fathur Rosi; Julianto, Eddy; Adithama, Stephanie Pamela (Universitas Atma Jaya Yogyakarta, 2025)
Opak Kopi Cafe faced operational challenges due to manual systems, such as paper-based order recording and direct message reservations to the owner, as well as the lack of performance reporting. In response, a website-based Point of Sale (POS) system was developed to streamline business processes. Its key features include online ordering and reservations for customers, order management by cashiers, and a dashboard and performance reporting for the owner, with Midtrans payment integration. The system, built using React Typescript, Express Typescript, and MySQL, proved successful. Functional and user testing results indicated that the website functioned well, making it easier for customers to order and reserve, while also helping the owner effectively monitor the cafe's performance. Kafe Opak Kopi menghadapi kendala operasional akibat sistem manual, seperti pencatatan pesanan di kertas dan reservasi melalui pesan langsung ke pemilik, serta ketiadaan laporan kinerja. Menanggapi hal ini, sebuah sistem Point of Sale (POS) berbasis website dikembangkan untuk mempermudah proses bisnis. Fitur utamanya mencakup pemesanan dan reservasi online bagi pelanggan, pengelolaan pesanan oleh kasir, serta dashboard dan laporan kinerja untuk pemilik, dengan integrasi pembayaran Midtrans. Sistem yang dibangun menggunakan React Typescript, Express Typescript, dan MySQL ini terbukti berhasil. Hasil pengujian fungsional dan pengguna menunjukkan bahwa website telah berfungsi baik, mempermudah pelanggan dalam memesan dan reservasi, sekaligus membantu pemilik memantau kinerja kafe secara efektif. Kata Kunci: Point of Sale, Pemesanan Online, Typescript, Reservasi Online